ANALISIS STRATEGI PENGEMBANGAN BISNIS DENGAN PENDEKATAN BISNIS MODEL CANVAS (BMC) DAN SWOT - Riscal, Detty Agustin; Sri, Sahbany (Institut Agama Hindu Negeri Gde Pudja Mataram, 2024)
Cinnamonstory.id is a handover and dowry decoration business that was formed in 2017. The objectives of this study are analyzing the mapping of the 9-element Business Model Canvas (BMC) business model with SWOT analysis (Strength, Weakness, Opportunity and Threats); Formulate a business model development strategy Cinnamonstory.id using the SWOT matrix. The analysis method in this study uses a combination of BMC analysis approach and SWOT matrix in formulating Cinnamonstrody.id business development strategy. The results of the SWOT analysis show that Cinnamonstory.id in Quadrant II is a diversification. The results of the study show training, design innovation, affordable, responsive services, and effective digital marketing are the keys to Cinnamonstory.id success, develop Cinnamonstory.id by joining a network of vendors, offering consulting and leasing, recruiting and training employees, and establishing partnerships with suppliers, seek new ideas, develop distinctiveness, improve operational efficiency, manage suppliers, and provide superior customer service in Cinnamonstory.id. and analyze customer feedback and sales data, allocate funds for promotions and investments, and develop marketing strategies and partnerships through social media.